DESCRIPTIVE ANALYSIS OF SOCIO-CULTURAL MEANING IN THE RORASA OF TERNATE TRADITIONAL WEDDING IN TUBO VILLAGE, NORTH TERNATE CITY DISTRICT - Anwar Nada (SOSIOEDUKASI, 2025)
This study aims to analyze descriptively the social and cultural meanings contained in the rorasa procession as part of the Ternate traditional wedding in Tubo Village, North Ternate City District. Rorasa is one of the important traditions that contains symbolic, social, and spiritual values in the lives of the Ternate people. The method used is a descriptive qualitative approach , with data collection techniques through observation, in-depth interviews with traditional figures, bridal couples, and community leaders, as well as field documentation. The results of the study show that rorasa not only functions as a traditional ritual, but also has a meaning as a reinforcement of cultural identity, strengthening social ties between families, and a means of preserving the noble values of the Ternate community , such as respect, togetherness, and social responsibility. This tradition also reflects the important position of family and community in the traditional marriage system. However, modernization and changes in lifestyle have begun to affect the implementation of rorasa, so that efforts are needed to preserve and revitalize the cultural values contained therein.